KAPASITAS ADSORPSI LOGAM MANGAN (Mn) MENGGUNAKAN BIOSORBEN PEKTIN DARI KULIT PISANG KEPOK - Mardhiyah Nadir; Sitti Sahraeni; Rifka Aulia Mawardi; Marlinda Marlinda (Politeknik Negeri Samarinda, 2022)
The construction of a chemical plant has a negative impact on the environment by producing waste containing heavy metals such as manganese (Mn). One of the treatments of waste containing heavy metals by adsorption method. The use of pectin as a biosorbent in the adsorption process has been widely carried out because it has several advantages and contains active groups such as carboxyl and hydroxyl which play an important role in the adsorption process. This research aimed to determine the adsorption capacity of manganese (Mn) using pectin from kepok banana peel as a biosorbent. Pectin was obtained from the extraction of kepok banana peels using the Microwave Assisted Extraction (MAE) method. Manganese solution was adsorbed using 1 gram mass of pectin with variable adsorption time (60, 90, 120, 150, and 180 minutes). Identification of pectin functional groups at absorption wavelengths between 1000cm-1 to 3500 cm-1 using FT-IR spectrophotometer and the analysis results obtained that there are hydroxyl groups (3423,993 cm-1), carbonyl (1638,233 cm-1), carboxylate (1736.585 cm-1), ether (1079.942 cm-1) and carbocyclic (1238.076 cm-1). Mn metal after adsorption was analyzed using AAS. The results showed that the optimum adsorption time to adsorb Mn metal was 150 minutes with an adsorbed metal capacity of 0.182 mg/g (36.403%). The adsorption of Mn followed the Freundlich isotherm equation with KF = 0.0886 mg/g. Keywords: adsorption, adsorption isotherm, adsorption capacity, Mn metal, pectin